2D vanadium carbide MXenzyme to alleviate ROS-mediated inflammatory and neurodegenerative diseases - Wei Feng (Nature Portfolio, 2021)
Materials with enzymatic-like activities are of interest for a wide range of applications. Here, the authors report on 2D vanadium carbide MXene nanozymes capable of mimicking multiple enzymes and demonstrate application to treat reactive oxygen species-mediated inflammatory and neurodegenerative diseases.